2011
DOI: 10.1105/tpc.111.086827
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Pathway to Astaxanthin in the Flowers of Adonis aestivalis    

Abstract: A few species in the genus Adonis are the only land plants known to produce the valuable red ketocarotenoid astaxanthin in abundance. Here, we ascertain the pathway that leads from the b-rings of b-carotene, a carotenoid ubiquitous in plants, to the 3-hydroxy-4-keto-b-rings of astaxanthin (3,39-dihydroxy-b,b-carotene-4,4'-dione) in the blood-red flowers of Adonis aestivalis, an ornamental and medicinal plant commonly known as summer pheasant's eye. Two gene products were found to catalyze three distinct react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 71 publications
1
86
0
Order By: Relevance
“…It has been suggested that in Adonis plants, the synthesis of a 3-hydroxy-4-keto-β(beta)-ionone ring from the β(beta)-ionone ring substrate is controlled by two genes and occurs in three steps [ 99 ]. First, a 4-hydroxy-β(beta)-ring is formed by carotenoid-β(beta)-ring-4-dehydrogenase (CBFD); second, 4-hydroxy-β(beta)-ring-4-dehydrogenase (HBFD) continues with the further dehydrogenation of carbon 4 giving a keto group at this position; and third, CBFD introduces a hydroxyl group at carbon 3 of the 4-keto-β(beta)-ring to form the 3-hydroxy-4-keto-β(beta)-ring.…”
Section: Astaxanthin Biosynthesis In X Dendrorhous and In Other Orgamentioning
confidence: 99%
“…It has been suggested that in Adonis plants, the synthesis of a 3-hydroxy-4-keto-β(beta)-ionone ring from the β(beta)-ionone ring substrate is controlled by two genes and occurs in three steps [ 99 ]. First, a 4-hydroxy-β(beta)-ring is formed by carotenoid-β(beta)-ring-4-dehydrogenase (CBFD); second, 4-hydroxy-β(beta)-ring-4-dehydrogenase (HBFD) continues with the further dehydrogenation of carbon 4 giving a keto group at this position; and third, CBFD introduces a hydroxyl group at carbon 3 of the 4-keto-β(beta)-ring to form the 3-hydroxy-4-keto-β(beta)-ring.…”
Section: Astaxanthin Biosynthesis In X Dendrorhous and In Other Orgamentioning
confidence: 99%
“…5E) suggested that this compound had fewer conjugated double bonds than β-carotene. A study of the literature for rare carotenoids found in plants provided many possibilities (21)(22)(23)(24), but none seemed more likely than β-carotene-5,6-epoxide, a carotenoid that has previously been observed in photosynthetic tissues (21). β-carotene-5,6-epoxide was synthesized (25) and subjected to HPLC analysis, where it eluted at the same time and with the same spectrum as the unknown carotenoid ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The high β-carotene line used in this study (RI) derives from the crossing of the cultivated tomato S. lycopersicum [LA4024 in the Tomato Genetics Resource Center (TGRC) database] with the wild S. galapagense accession (LA0483 in the TGRC database) (12,13). Two ZW events (10)(11)(12)(10)(11)(12)(13)(14)(15)(16)(17) were crossed with two RI lines (RI33 and RI1). The lines were cross-pollinated.…”
Section: Methodsmentioning
confidence: 99%
“…However, on a production cost-basis, a plant-based source remains the most economically viable (8,9). The only plant capable of ketocarotenoid (astaxanthin/phoenicoxanthin) formation is Adonis aestivalis, which is not amenable to agricultural production and contains toxic alkaloids (10,11). Thus, a genetic engineering approach of an agricultural crop offers a viable alternative.…”
mentioning
confidence: 99%